The diagnostic accuracy of pericolonic fat extension and attenuation for colorectal tumors. Issue 9 (September 2015) - Zeina, Abdel-Rauf; Mahamid, Ahmad; Walid, Saliba; Nachtigal, Alicia; Shapira-Rootman, Mika
Highlights: Pericolonic fat extent and attenuation were higher in stage ≥T3 than <T3 tumors. The sensitivity of pericolonic fat infiltration in detecting ≥T3 tumors was 95% and the specificity 20%. Pericolonic fat extent, pericolonic fat attenuation, and maximal tumor diameter were assessed. The application of all three parameters achieves 100% specificity. Abstract: Objective: To evaluate the utility of quantitative analysis of the extension and attenuation of pericolonic fat in the local staging of colorectal cancer (CRC) using multi detector computed tomography (MDCT). Materials and methods: This was a retrospective study of 110 patients who were operated due to pathologically proven CRC from January 2007 to January 2010, and who underwent preoperative MDCT of the abdomen and pelvis with administration of intravenous contrast material and image acquisition during the portal venous phase. The mean age was 69 years (range of 38–90 years). Pathological reports were reviewed for TNM staging. All MDCT studies were reviewed by two certified radiologists for maximal and minimal tumor diameter, extent of the infiltrated pericolonic fat (measured in mm), attenuation of the infiltrated pericolonic fat (measured in Hounsfield units), and attenuation of normally appearing fat next to the tumor. The sensitivity and specificity of these parameters in detecting patients with ≥ T3 CRC were calculated. Results: The overall sensitivity, specificity, and accuracy of pericolonic fat infiltration in detecting patients with ≥T3 stage were 95% (95% CI, 89.0–98.7%), 20% (5.8–43.7%), and 81.9% (74.7–89%) respectively. The mean extent and attenuation of the infiltrated pericolonic fat, in addition to the maximal tumor diameter, were higher in the ≥T3 group ( p < 0.05). By defining threshold values to these parameters, the positive predictive value for detecting ≥T3 stage tumors approaches 100%. Conclusion: Quantitative analysis of pericolonic fat increased the accuracy of MDCT in the detection of local tumor spread in CRC.